Экспериментальное и теоретическое исследование деформированного состояния металла при прокатке швеллера - Ершов, С. В.; Мельник, С. Н.; Геймур, К. Г.; Кравченко, Е. А. (НТУ "ХПИ", 2014)
Несмотря на большое количество экспериментальных исследований швеллеров, закономерности поведения металла при прокатке в калибрах швеллерной формы изучены недостаточно. Изложены результаты сопоставления данных экспериментального и теоретического исследования деформированного состояния швеллера при прокатке в 9 клети среднесортного стана 350 ПАО «ДМКД». Рассмотрено и проанализировано формоизменение металла в различных сечениях раската. Установлено наличие значительной неравномерности распределения уширения и вытяжки в очаге деформации, установлены закономерности их распределения.

Forms are not well understood despite the proliferation of them and a large number of experimental studies of the behavior of the metal during rolling in passes trough. The article presents the results of comparing the data of the experimental and theoretical studies of strain state of channels at rolling mill in 9 medium-section mill 350 PJSC «DMK». Was reviewed and analyzed metal forming in various sections of roll – at the entrance of the deformation zone, during the steady rolling process and the output of the roll P. The article conclusions about the presence of the very uneven distribution of broadening and hoods in the deformation zone, the regularities of their distribution.
Experimental and theoretical study of strain state of the metal during rolling channel
Keywords: фланцевые профили; швеллера; калибры; течение металла; deformation; flange profiles; channel; calibre; metal flow